The door of the caliph - Cardoso, Elsa, 1989- author.
1 online resource
Keywords: "This book focuses on the conceptualization of the court, palace and ruler of the Umayyad Caliphate of al-Andalus. Western terminology still plays a normative role in the representation of foreign courts, determining concepts that fit poorly into chronologies with their own dynamics and specificities, which is the case of Muslim courts. While Court Studies is a well-developed field for modern Western societies, Muslim medieval courts lack a consistent field of research. Sources elaborate a specific terminology for medieval Muslim court societies. In the specific case of the Umayyad Caliphate of al-Andalus, the court is usually articulated as Bāb Suddat al-Khalīfa ("The door of the Sudda of the caliph") - a reference to the symbology of the main city gate of Cordoba - or simply as Bāb. Bāb Suddat al-Khalīfa became the most emblematic concept to name the Umayyad palace and its society, which will be additionally interpreted in the framework of the performance of ceremonial. The strong conceptualization of the Umayyad court of Cordoba was highlighted through the articulation of ceremonial, as the mis-en-scène of the conceptualization, expressed by gestures, insignia and hierarchies. The preliminary comparative perspective with the Umayyad Caliphate of Damascus, the 'Abbasid and Fatimid Caliphates, and the Byzantine Empire further discusses the Umayyad Andalusi model in relation to other dynasties. While the book focuses on the Umayyad conceptualization and articulation of ceremonial, this model will be discussed within the Mediterranean and Eastern framework of the tenth and 11th centuries, which broadens the interest of the book to other fields of research"--